Collaborative network platform for multi-site production - Arrais-Castro, António (2012)
The Competition in the global economy is intensifying the implementation of web-based collaboration platforms to improve the personalized interaction between clients and producers. Agility in the order-production-delivery cycle is a key element for industrial enterprises as a means to meet the requirements of this paradigm. Agile/Virtual Enterprise based scenarios are characterized by large product variety dependent on product specific requirements of individual customers. Therefore, to enable an enriched network based tool for Virtual Enterprise specification and configuration, there is a need to define a collaborative environment for dynamically enable candidate business partners to integrate it. In this paper, we propose a web platform and describe its main functionalities for interactive multi-site production network integration. © 2012 Springer-Verlag.